Evaluasi Peraturan Walikota Denpasar No.09 Tahun 2009 Tentang Penataan dan Pembinaan Pasar Tradisional, Pusat Perbelanjaan, dan Toko Modern - Nurdiana, Yuda Ike; Winaya, I Ketut; Sastra Wijaya, Komang Adi (CITIZEN CHARTER, 2020)
ABSTRACT Denpasar Mayor Regulation no.09 of 2009 concerning arrangement and coaching traditional markets, shopping centers and modern shops in reducing the growth of modern stores in the South Denpasar and suppressing the growth rate of modern shops that are not in accordance with established regulations. This regulation is lacking because there are many modern shops stand in the District of South Denpasar not in accordance distance that has been determined and don’t have parking space, causing congestion on the Panjer road. These problems have led to miscommunication between the government and modern shop business entities that want to take care of modern store business permit (IUTM). The research method used in research is descriptive qualitative. To obtain data, authors conducted in-depth field observations with informants related to this regulation. The findings of this study indicate that there are many modern stores that stand without a permit from the government or modern. Keywords: Evaluation, Arrangement and Construction